Sikopansi: Seni Membudak dalam Ritus Penindasan - Indra Setia Bakti; Muklir Muklir; Sufi Sufi (Sociology Department Of Syiah Kuala University, 2022)
This study aims to explore the practice of sycophants in the office. We used observation and literature study as methods. We analyzed the data obtained from observations and document studies dialectically. The results showed that the behavior of sycophants as an individual initiative in the organizational arena institutionalized the habitus of a sycophant. The sycophants who lack the capability and professionalism have succeeded in politicizing the situation in the office for their interests through various oppression rites. Dominative social relations have created a toxic work environment and killed the desire of other staff to be creative and innovate. As a result, government organizations carry out routine tasks, but hard to come up with brilliant ideas in assisting community services because many of their employees no longer believe in the career path system in their office.AbstrakStudi ini bertujuan untuk mengeksplorasi praktik sikopansi di lingkungan kerja. Peneliti menggunakan metode observasi dan studi literatur. Data yang diperoleh dari hasil pengamatan lapangan dan kajian dokumen dianalisis secara dialektis. Hasil penelitian menunjukkan bahwa perilaku menjilat atasan sebagai prakarsa individu dalam arena organisasi yang menginstitusionalisasi habitus sikopan. Para sikopan yang minim kapabilitas dan profesionalitas berhasil memolitisasi situasi yang terjadi di lingkungan kerja untuk kepentingan pribadinya melalui berbagai ritus penindasan. Relasi sosial yang bersifat dominatif melahirkan lingkungan kerja toksik yang membunuh semangat staf lain dalam berkreativitas dan berinovasi. Alhasil organisasi pemerintahan berjalan dalam skema pelaksanaan rutinitas kerja namun agak sulit menelurkan ide-ide brilian dalam pelayanan masyarakat karena banyak pegawai yang tidak percaya lagi dengan sistem jenjang karier di kantornya.